Effects of a 5-HT1B Receptor Agonist on Locomotion and Reinstatement of Cocaine-Conditioned Place Preference after Abstinence from Repeated Injections in Mice - Der-Ghazarian, Taleen S.; Call, Tanessa; Scott, Samantha N.; Dai, Kael; Brunwasser, Samuel J.; Noudali, Sean N.; Pentkowski, Nathan S.; Neisewander, Janet L. (Frontiers in Systems Neuroscience, 2017)
5-HT1B receptors (5-HT1BRs) modulate behavioral effects of cocaine. Here we examined the effects of the 5-HT1BR agonist CP94253 on spontaneous and cocaine-induced locomotion and on cocaine-primed reinstatement of conditioned place preference (CPP) in male mice given daily repeated injections of either saline or cocaine (15 mg/kg, IP) for 20 days. In the locomotor activity experiment, testing occurred both 1 and 20 days after the final injection. In the CPP experiment, mice underwent conditioning procedures while receiving the last of their daily injections, which were given either during or ≥2 h after CPP procedures. The CPP procedural timeline consisted of baseline preference testing (days 12-13 of the chronic regimen), conditioning (days 14-19, 2 daily 30-min sessions separated by 5 h), CPP test (day 21), extinction (days 22-34; no injections), CPP extinction test (day 35; no injections), and reinstatement test (day 36). Mice that had not extinguished received additional extinction sessions prior to reinstatement testing on day 42. On test days, mice were pretreated with either saline or CP94253 (10 mg/kg, IP). Testing began 30 min later, immediately after mice were primed with either saline or cocaine (5 mg/kg for locomotion; 15 mg/kg for reinstatement). We found that CP94253 increased spontaneous locomotion in mice receiving repeated injections of either saline or cocaine when tested 1 day after the last injection, but had no effect on spontaneous locomotion after 21 days abstinence from repeated injections. Surprisingly, cocaine-induced locomotion was sensitized regardless of whether the mice had received repeated saline or cocaine. CP94253 attenuated expression of the sensitized locomotion after 20 days abstinence. A control experiment in noninjected, drug-naïve mice showed that CP94253 had no effect on spontaneous or cocaine-induced locomotion. Mice reinstated cocaine-CPP when given a cocaine prime, and CP94253 pretreatment attenuated the cocaine reinstatement. The findings suggest that stress from repeated saline injections cross-sensitizes cocaine locomotion and that CP94253 attenuates this effect, as well as reinstatement of cocaine-CPP. This study supports the idea that 5-HT1BR agonists may be useful anti-cocaine medications.